2004
DOI: 10.1212/01.wnl.0000115106.88813.5b
|View full text |Cite
|
Sign up to set email alerts
|

Indian Agarwal megalencephalic leukodystrophy with cysts is caused by a common MLC1 mutation

Abstract: Indian patients with megalencephaly and MRI changes that show extensive white matter changes with temporal cysts should raise suspicion for MLC. Members of the Agarwal ethnic group affected with the disorder present with a mildly progressive course and show a common mutation (320insC) in the MLC1 gene, suggesting a founder effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 13 publications
(16 reference statements)
1
76
0
1
Order By: Relevance
“…Little information regarding the average life span in MLC is available, because this disease was defined only recently (1). Some reported patients have died in their teens or twenties, but several adult cases of MLC have been reported (3,4,8,14,15). The patient described in the present case was over 50 years old at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Little information regarding the average life span in MLC is available, because this disease was defined only recently (1). Some reported patients have died in their teens or twenties, but several adult cases of MLC have been reported (3,4,8,14,15). The patient described in the present case was over 50 years old at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is typically described as occuring in the Agarwal community of India [19]. It generally presents in infancy with macrocephaly, often in combination with mild gross motor and cognitive decline, gradual onset of ataxia, spasticity and relatively late onset of mild mental deterioration.…”
Section: Dysmyelinating Diseasementioning
confidence: 99%
“…[4,5] In India, majority of the patients belong to the Agarwal community. [6,7] Our patient however did not belong to this community. Indian patients with megalencephaly and MR changes that show extensive white matter changes with temporal cysts should raise suspicion for MLC.…”
Section: Case Reportmentioning
confidence: 68%
“…Indian patients with megalencephaly and MR changes that show extensive white matter changes with temporal cysts should raise suspicion for MLC. [7] This disease has been assigned to the gene, MLC1, and is localized on chromosome 22qtel. [8] It has been reported that no basic biochemical defect was identified in patients with VML.…”
Section: Case Reportmentioning
confidence: 99%